IMPLEMENTASI SYSTEM USABILITY SCALE UNTUK PENGEMBANGAN MODEL COMPUTER BASED TEST PADA PESANTREN NAFIDATUNNAJAH - Galuh Saputri; Agung Siswopranoto (Institut Sains dan Teknologi Nasional, 2022)
ABSTRACT It has been a year since the Covid-19 pandemic has occurred in Indonesia, starting from the tourism sector, the economy, and others including education. Of course, the learning and assessment process becomes difficult to carry out, one of which is at the Nafidatunnajah Islamic Boarding School which is located on the border in Rawakalong, Gunung Sindur, Bogor Regency. The Nafidatunnajah Islamic Boarding School has formal education including vocational education, MTS, and MI. Information technology and computers which can now be used are very important factors in the world of education, from offline face-to-face learning to online using e-learning, Zoom meetings, including changing Paper Based Tests to Computer Based Tests (CBT). This research uses Rapid Application Development (RAD) software model and Unified Modeling Language tools. With the development of this CBT model, it is hoped that it can provide a solution for testing the entrance test which will be measured using the System Usability Scale method. For teachers, the user responses were taken by 10 teachers and for prospective students, the user responses were taken for 20 students by being tested using a web-based CBT application on a browser on each computer, then filling out a questionnaire sheet. The output obtained by using the System Usability Scale in this application is ease of use, more practical and faster, this is stated by prospective students by 77% and teachers by 76%. Keywords: Computer Based Test, RAD, Web, Unified Modelling Language, System Usability Scale